"Kuitenkaan ihminen ei voi voittaa vuorta" : japanilaisen Wandervogel-klubin jäsenten käsitykset vaeltamisesta ja vuorista - Laasanen, Petteri (2012)
Instigated by the author’s four-and-a-half month long membership in the Wandervogel hiking club of Kanazawa University, Japan, this study focuses on the experience of hiking in the mountains from a phenomenological perspective. This period of preliminary fieldwork is drawn upon as a source of inspiration and firsthand experience rather than as research material itself, the bulk of which consists of twelve answers given by members of Wandervogel in an unstructured Google Docs questionnaire. Both during and after the lengthy process of translating these answers from Japanese into Finnish, the method of close reading was applied in order to not only uncover their apparent content but to point out possible implicit connotations as well.